Wild experiment: feeling science and secularism after Darwin - Schaefer, Donovan O. (Duke University Press, 2022)
The longing to believe : philosophers on conspiracy theory and the sense of science -- Sensualized epistemology : affect theory on how reason gets racialized -- Science as an intoxication : secularism studies on enchantment and critique -- Feeling is believing : perspectives on cogency theory from neuroscience and experimental psychology -- Only better beasts : Darwin, Huxley, and the sense of science -- The secular circus : science and racialized reason in the Scopes Trial -- New atheism as secular conspiracy theory.